Orphan Drug Use in Patients With Rare Diseases: A Population-Based Cohort Study - Gorini, Francesca; Santoro, Michele; Pierini, Anna; Mezzasalma, Lorena; Baldacci, Silvia; Bargagli, Elena; Boncristiano, Alessandra; Brunetto, Maurizia Rossana; Cameli, Paolo; Cappelli, Francesco; Castaman, Giancarlo; Coco, Barbara; et al. (Frontiers in Pharmacology, 2022)
Background: Orphan drugs are used for the diagnosis, prevention and treatment of rare diseases that, in the European Union, are defined as disorders affecting no more than 5 persons in 10,000. So far, a total of around 800 orphan medicinal products have been approved by the European Medicines Agency, however the utilization profile of orphan drugs has yet to be explored. This study aimed at assessing the utilization profile of orphan drugs authorized for marketing by the Italian Medicines Agency using population-based data. Methods: A total of 21 orphan drugs used in outpatient settings, approved in the European Union before or during the 2008–2018 period and involving 15 rare diseases, were included in the study. The monitored population included patients with one of the conditions surveilled by the population-based Tuscany Registry of Rare Diseases and diagnosed between 2000–2018. A multi-database approach was applied, by linking data from the registry with information collected in drug prescriptions databases. The prevalence and intensity of use were estimated for the selected orphan drugs and other non-orphan medications, used to treat the same rare disease and for which a change in the prevalence of use was hypothesized after authorization of the orphan drug. Results: For some diseases (acquired aplastic anemia, tuberous sclerosis complex, most metabolic diseases) a low prevalence of orphan drugs use was observed (range between 1.1–12.5%). Conversely, orphan drugs were frequently used in hemophilia B, Wilson disease and idiopathic pulmonary fibrosis (maximum of 78.3, 47.6 and 41.8%, respectively). For hemophilia B and Leber’s hereditary optic neuropathy, there are currently no other medications used in clinical practice in addition to orphan drugs. Six orphan drugs were used for the treatment of pulmonary arterial hypertension, appearing the elective therapy for this disease, albeit with different utilization profiles (range of prevalence 1.7–55.6%). Conclusion: To the best of our knowledge, this is the first study investigating the utilization profile of orphan drugs prescribed in a defined geographical area, and providing relevant information to monitor over time potential changes in the prevalence of these medications as well as in the health care decision making.